Pretransplant IgA-Anti-Beta 2 Glycoprotein I Antibodies As a Predictor of Early Graft Thrombosis after Renal Transplantation in the Clinical Practice: A Multicenter and Prospective Study - Morales, Jose M.; Serrano, Manuel; Martinez-Flores, Jose Angel; Gainza, Fracisco Javier; Marcen, Roberto; Arias, Manuel; Escuin, Fernando; Pérez, Dolores; Andres, Amado; Martínez, Miguel Angel; Maruri, Naroa; Alvarez, Eva; et al. (Frontiers in Immunology, 2018)
Background Graft thrombosis is a devastating complication after renal transplantation. We recently described the association of anti-beta-2-glycoprotein-I (IgA-ab2GP1) antibodies with early graft loss mainly caused by thrombosis in a monocenter study. Methods Multicenter prospective observational cohort study. Setting and participants Seven hundred forty patients from five hospitals of the Spanish Forum Renal Group transplanted from 2000 to 2002 were prospectively followed-up for 10 years. Outcomes Early graft loss and graft loss by thrombosis. Measurements The presence of IgA anti-B2GP1 antibodies in pretransplant serum was examined using the same methodology in all the patients. Results At transplantation, 288 patients were positive for IgA-B2GP1 (39%, Group-1) and the remaining were negative (Group-2). Graft loss at 6 months was higher in Group-1 (12.5 vs. 4.2% p < 0.001), vessel thrombosis being the most frequent cause of early graft loss, especially in Group-1 (6.9 vs. 0.4% p < 0.001). IgA-aB2GP1 was the most important independent risk factor for graft thrombosis (hazard ratio: 13.83; 95% CI: 3.17–60.27, p < 0.001). Furthermore, the, presence of IgA-aB2GP1 was associated with early graft loss and delayed graft function. At 10 years, survival figures were also lower in Group-1: graft survival was lower compared with Group-2 (60.4 vs. 76.8%, p < 0.001). Mortality was significantly higher in Group-1 (19.8 vs. 12.2%, p = 0.005). Limitations Patients were obtained during a 3-year period (1 January 2000–31 December 2002) and kidneys were only transplanted from brain-dead donors. Nowadays, the patients are older and the percentage of sensitized and retransplants is high. Conclusion In a prospective observational multicenter study, we were able to corroborate that pretransplant presence of IgA-aB2GP1 was the main risk factor for graft thrombosis and early graft loss. Therefore, a prospective study is needed to evaluate the efficacy and safety of prophylactic anticoagulation to avoid this severe complication.